The Effects of Low-Risk Drinking on Neurocognition Among Older Persons Living with HIV as Compared to Those Without HIV - Kohli, Maulika (Alcohol Clin Exp Res, 2020)
BACKGROUND: Heavy alcohol use negatively impacts neurocognition, but some studies report neurocognitive benefits associated with light drinking among HIV-seronegative (HIV-) older persons, suggesting a non-linear or an inverted “J-shaped” association of alcohol consumption on neurocognition. Alcohol use is common among people with HIV (PWH), however, the association between recent “low-risk” alcohol consumption and neurocognition among PWH is poorly understood. METHODS: Participants included 310 PWH and 89 HIV- older (≥50 years) adults who reported alcohol abstinence or “low-risk” drinking, defined per the National Institute on Alcohol Abuse and Alcoholism criteria (i.e., ≥15 drinks/week or ≥5 drinks/day for men; ≥8 drinks/week or ≥ 4 drinks/day for women). Neurocognition was measured using global and domain-specific demographically-corrected T-scores. Multiple linear regressions examined the interaction between total drinks in the last 30 days (linear and quadratic terms) and HIV serostatus on neurocognition, covarying for age, sex, lifetime Major Depressive Disorder, lifetime non-alcohol substance use disorders, and lifetime alcohol use disorder. RESULTS: Total drinks consumed in the last 30 days did not differ by HIV serostatus (p=.202). Among HIV- older adults, quadratic effects of total drinks on neurocognition occurred such that optimal neurocognition (i.e., global function, executive function, learning, delayed recall, and motor skills) was detected at intermediate levels of “low-risk” drinking (~20 to 40 drinks), with poorer performance at the lower and higher ranges of “low-risk” consumption. In PWH, total drinks did not exhibit linear or quadratic associations with neurocognition. CONCLUSIONS: In HIV- “low-risk” drinkers, intermediate levels of recent alcohol use were associated with better neurocognition, consistent with the inverted J-shaped association. The same non-linear effect of recent alcohol consumption on neurocognition was absent in PWH indicating there may be no beneficial or deleterious effects of low-risk alcohol consumption on neurocognition among PWH. Future research is warranted to examine associations between alcohol consumption and HIV-related biopsychosocial disadvantages that may supersede the neurocognitive benefits of alcohol.